The Relationship between Online Gaming Intensity and Discipline in Performing Obligatory Prayers - Nisa Ul Anbiya; Saifullah Saifullah; Zubaidah Zubaidah (Jurnal Ilmiah Guru Madrasah, 2026)
The rapid expansion of digital technology has increased children's engagement with online games, raising concerns regarding its influence on religious behavior within Islamic educational settings. Despite extensive research on the academic and social consequences of online gaming, empirical evidence addressing its association with students’ religious discipline remains limited, particularly at the Madrasah Ibtidaiyah level. This research examined the relationship between online gaming intensity and discipline in performing obligatory prayers among students of MIN 12 Nagan Raya. A quantitative correlational design was employed involving 53 students selected through purposive sampling. Data were gathered through validated and reliable questionnaires and analyzed using Pearson Product–Moment correlation and simple linear regression techniques. Statistical analysis demonstrated a significant negative correlation between online gaming intensity and prayer discipline (r = −0.451, p = 0.001). The regression results further indicated that online gaming intensity accounted for 20.3% of the variance in students’ prayer discipline (R² = 0.203). These findings indicate that increased involvement in online gaming tends to coincide with lower consistency in fulfilling obligatory prayers. The study contributes to the growing discourse on digital behavior and Islamic education by demonstrating that technology-related activities may influence not only academic and social dimensions but also the spiritual development of young learners. Consequently, strengthening cooperation between schools and families is necessary to encourage responsible digital engagement, foster self-regulation, and support the development of students’ religious character in the contemporary digital environment.